PENGARUH KEPUTUSAN KEUANGAN, STRATEGI DIVERSIFIKASI, EFISIENSI OPERASIONAL DAN INOVASI TERHADAP NILAI PERUSAHAAN - Muhammad Wildan; Nur Wachidah Yulianti (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2021)
The purpose of this research is to find the effects of financial decision, diversification strategy, operational efficiency, and innovation on firm value. This research using a sample of thirteen consumer goods companies listed on Indonesia Stock Exchange in 2015-2019. The method used is purposive sampling. Methods of data analysis used in this research is multiple linier regression analysis. The result of this research show the variables investment decision and financing decision have a positive effect on firm value. Operational efficiency have a negative effect on firm value. The variables diversification strategy and innovation have no effect on firm value.